PEMBATALAN AKTA HIBAH OLEH SALAH SATU PEMBERI HIBAH MENURUT KOMPILASI HUKUM ISLAM (STUDI KASUS PUTUSAN PENGADILAN AGAMA CURUP NOMOR 282/PDT.G/2019/PA.CRP) - Dwiyana Novianturi; Imelda Martinel (Fakultas Hukum Universitas Tarumanagara, 2021)
The existence of an opportunity to withdraw grants from parents to children makes the function of grants unclear, resulting in no legal certainty. The problem in this research is how is the legal certainty of the cancellation of the grant deed by one of the grantors according to the Islamic Law Compilation in the case of the Curup Religious Court Decision Number 282 / Pdt.G / 2019 / PA.Crp? The research method used is juridical normative using primary data and secondary data, and the results of research using qualitative data analysis methods. The results of the study show that the cancellation of the grant deed by one of the grantors according to the Compilation of Islamic Law in the case of the Curup Religious Court Decision Number 282 / Pdt.G / 2019 / PA.Crp is in accordance with Article 212 KHI. This is because the grant deed does not meet the legal requirements of the agreement according to Islamic law, which is not fulfilling the elements of mahallul 'aqd and the elements of mau'qud'alaih. However, court judges should be able to provide a sense of justice, both for parents as grants, and for children as grant recipients, namely the Chairperson of the Curup Religious Court's Panel of Judges can revise the grant made by Helmi Alexsander with Rika Afrianti that Yoan Alfathan Samudra is 1/3 of the total grant, so that the rest of the grant, is returned to Helmi Alexsander with Rika Afrianti.